1999
DOI: 10.1105/tpc.11.11.2233
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of the Endoplasmic Reticulum Retention Machinery Reveals Anterograde Bulk Flow

Abstract: We have studied the possible mechanisms of endoplasmic reticulum (ER) export and retention by using natural residents of the plant ER. Under normal physiological conditions, calreticulin and the lumenal binding protein (BiP) are efficiently retained in the ER. When the ER retention signal is removed, truncated calreticulin is much more rapidly secreted than truncated BiP. Calreticulin carries two glycans of the typical ER high-mannose form. Both glycans are competent for Golgi-based modifications, as determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 51 publications
0
73
0
11
Order By: Relevance
“…Its apparent molecular weight (60 kDa) falls within the usual mobility range (50-60 kDa) shown by calreticulins run on SDS-PAGE and corresponds to the M r detected for calreticulin isolated from tobacco germinating seeds (Denecke et al 1995). Since tobacco calreticulin carries two consensus sites for N-linked glycosylation (Denecke et al 1995), the observed size difference between spinach (54 and 56 kDa) and tobacco (60 kDa) calreticulins may be partly attributed to the presence of two high-mannose glycan chains on the tobacco calreticulin (Crofts et al 1999).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Its apparent molecular weight (60 kDa) falls within the usual mobility range (50-60 kDa) shown by calreticulins run on SDS-PAGE and corresponds to the M r detected for calreticulin isolated from tobacco germinating seeds (Denecke et al 1995). Since tobacco calreticulin carries two consensus sites for N-linked glycosylation (Denecke et al 1995), the observed size difference between spinach (54 and 56 kDa) and tobacco (60 kDa) calreticulins may be partly attributed to the presence of two high-mannose glycan chains on the tobacco calreticulin (Crofts et al 1999).…”
Section: Discussionmentioning
confidence: 67%
“…The localization of calreticulin in the Golgi apparatus, including Golgi-coated vesicles and, at a lower abundance, in the ER that we found in tobacco pollen tubes may reflect Golgi-ER protein recycling if we take into account that tobacco calreticulin also carries two glycan chains of the typical ER high-mannose form (Crofts et al 1999).…”
Section: Discussionmentioning
confidence: 94%
“…The signal peptide does not have a consensus amino acid sequence, but is characterised by three domains; the positively charged n-region on the N-terminus and a central hydrophobic h-region followed by a polar c-region containing the cleavage site. Second, classical cell wall proteins do not possess the C-terminal KDEL or HDEL tetrapeptide, the canonical ER retention motif recognised by the mechanism that serves to prevent secretion of enzymes resident in the lumen of this organelle [32,33].…”
Section: Identification Of Hypothetical and Classical Cell Wall Proteinsmentioning
confidence: 99%
“…For example, cells with a high secretory load can develop a more cisternal ER, indicating that increasing the internal dimensions of the ER increases its capacity for protein synthesis (Figure 2; Crofts et al, 1999;Stephenson and Hawes, 1986;Ridge et al, 1999). In addition, changes in ER morphology to a more cisternal form around sites of pathogen invasion and wounding have been documented, and defects in proteins that control ER cisternalisation (RTNs) affect the plant's susceptibility to invasion (Hardham et al, 2008;Takemoto et al, 2003;Hwang and Gelvin, 2004;Lee et al, 2012).…”
Section: Correlations Between Er Morphology and Functionmentioning
confidence: 99%
“…Often, the ER has proved to be more benign to heterologous proteins or even proteins normally localised in the vacuoles, leading to increased protein yields in transgenic plants. The ER appears to have an enormous potential for morphological change, as exemplified by the globular ER of considerable size found in calreticulin-overproducing tobacco plants (Crofts et al, 1999) that were otherwise growing normally. The growing knowledge of the processes associated with protein synthesis, storage, ER export and recycling from the Golgi, and the potential role(s) of ER 'shape' and dynamics in these processes now open up the prospect of engineering the secretory pathway to optimise heterologous protein production.…”
Section: Future Directionsmentioning
confidence: 99%